Probability of adoption of food safety in the production of organic fruits and vegetables in Mexico - Arroyo Cossio, Arturo Julián; Avendaño Ruiz, Belem Dolores; González Rodríguez, Zaira (Agricultura, Sociedad y Desarrollo, 2020)
The production of organic fruits and vegetables in Mexico has been successfully positioned in the international market. Most of its adherents are small-scale producers that are organized and directed towards production for exports. It is increasingly more complex to remain in this type of markets, since it is essential to guarantee the quality and food safety of the organic fruits and vegetables offered. Organic products have caused epidemiological outbreaks of diseases, which place at risk the health of consumers and the acceptance of these products in the market. Therefore, the characteristics and circumstances that lead to the adoption of standards of food safety must be identified. This study is carried out because most small-scale producers of organic fruits and vegetables in Mexico do not implement food safety standards. The probability of adoption of these standards by small-scale producers is determined with a probit analysis. The study was developed in eight states, among them Puebla, Jalisco and Veracruz, where 22 municipalities were visited, 56 producers of organic fruits and vegetables were interviewed, from which the institutional and production variables that represent the possibility of adopting food safety were determined. The model indicates that the probability of adoption of the standards depends not only on complying with the actions established by them, but also on commercial issues and of commitment with institutions and commercial contracts made by producers.